Reconstructing Islamic Education in the Age of Artificial Intelligence Toward a Human-Centered and Ethical Learning Paradigm - Ainul Jaria Maidin; Salma Begum; Maryam Rashid Saleh Al Tamimi; Muneera Mohammed Al Dossary; Abdallah El-Khatib (Al Husna: Jurnal Ilmiah Pendidikan Agama Islam, 2026)
This study aims to reconstruct Islamic education in the age of artificial intelligence by developing a human-centered and ethical learning paradigm. The rapid integration of AI in education has transformed learning processes, yet it raises significant ethical and pedagogical concerns, particularly in relation to human agency, moral development, and spiritual formation. The study employs a qualitative library research design using a systematic literature review approach of scholarly works. Data were analyzed through thematic content analysis to identify key themes related to Islamic education, AI integration, digital ethics, and human centered learning. The findings reveal that AI enhances educational efficiency through personalization, assessment automation, and accessibility; however, it also introduces challenges such as ethical risks, algorithmic bias, data privacy issues, and reduced human interaction. The study identifies that Islamic educational principles including taqwā, ‘adl, raḥmah, and adab provide a strong ethical foundation for guiding AI integration. The novelty of this research lies in the development of the Human-Centered Islamic AI Education Framework (HCAIEF), which integrates Islamic educational philosophy with contemporary AI ethics and human-centered learning theory. The study concludes that AI should function as a supportive tool that enhances, rather than replaces, human, moral, and spiritual dimensions of education.